Phytochemical analysis, cytotoxic, antioxidant and anti-diabetic activities of the aerial parts of Sorghum halepense - Muhammad Abdur Rehman Shah; Rahmat Ali Khan; Mushtaq Ahmed (Bangladesh Pharmacological Society, 2019)
Phytochemical screening, cytotoxic activity, total phenolic content, antioxidant and anti-diabetic activities of the Sorghum halepense methanolic extract and its different fractions were evaluated. Methanolic extract and its various fractions revealed the presence of reducing sugars, tannins, steroids,  glycosides, flavonoids in the methanolic extract where they were absent in n-hexane fraction except flavonoids. Gums and saponins were absent in all the samples. Methanolic extract indicated the highest cytotoxic (80.7 ± 1.3%) and anti-diabetic (62.5%) activities. The maximum total phenolic contents (28.7 ± 1.4 mg/mL) were found in the chloroform fraction. An aqueous fraction expressed the highest antioxidant activity 74.1 and 97.1% free radical scavenging properties in DPPH and ABTS assays respectively whereas, in the case of H2O2, methanolic extract indicated maximum (36.9%) activity. In conclusion, the extract of aerial parts of S. halepense is a source of compounds against cancer, diabetic and free radical associated disorders.